THE NOVEL “THE UNWOMALNY FACE OF WAR” OF S. ALEXIEVICH AS A CYCLIC DOCUMENTARY-FICTIONAL PROSE: STRUCTURE AND POETICS - Karolina Górska (RUDN Journal of Studies in Literature and Journalism, 2018)
The research focuses on the issues of cyclization in the documentary fictional prose of the famous writer. It is important to understand the content of the concepts of “cycle” and “cyclization” and the features of their manifestation in modern prose texts. The subject of analysis is the work by S. Alexievich “The Unwomanly Face of War” and ways to connect individual stories into one. We investigate the system of motive, which provides the artistic unity of the novel.